Induction of PI3K/Akt-Mediated Apoptosis in Osteoclasts Is a Key Approach for Buxue Tongluo Pills to Treat Osteonecrosis of the Femoral Head - Wang, Dan; Liu, Yicheng; Tang, Dandan; Wei, Shujun; Sun, Jiayi; Ruan, Lvqiang; He, Lin; Li, Ruolan; Ren, Qiang; Tian, Xiaoping; Chen, Yunhui (Frontiers in Pharmacology, 2021)
Buxue Tongluo Pill (BTP) is a self-made pill with the functions of nourishing blood, promoting blood circulation, dredging collaterals, and relieving pain. It consists of Angelica sinensis (Oliv.) Diels, Pheretima aspergillum (E.Perrier), Panax notoginseng (Burk.) F. H. Chen, Astragalus membranaceus (Fisch.) Bge, and Glycyrrhiza uralensis Fisch. Various clinical practices have confirmed the therapeutic effect of BTP on osteonecrosis of the femoral head (ONFH), but little attention has been paid to the study of its bioactive ingredients and related mechanisms of action. In this study, UPLC/MS-MS combined with GEO data mining was used to construct a bioactive ingredient library of BTP and a differentially expressed genes (DEGs) library for ONFH. Subsequently, Cytoscape (3.7.2) software was used to analyze the protein-protein interaction between BTP and DEGs of ONFH to screen the key targets, and functional annotation analysis and pathway enrichment analysis were carried out. Finally, 34 bioactive compounds were screened, which acted on 1232 targets. A total of 178 DEGs were collected, and 17 key genes were obtained after two screenings. By bioinformatics annotation on these key genes, a total of 354 gene ontology (GO) functional annotation analyses and 42 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were obtained. The present study found that GO and KEGG enrichment were mainly related to apoptosis, suggesting that BTP may exert an anti-ONFH effect by promoting osteoclast apoptosis. Experiments in vitro demonstrated that BTP could increase mitochondrial membrane potential (MMP) and induce remarkable apoptosis in osteoclasts. Furthermore, we determined the apoptosis marker of Cleaved(C)-caspase-3, bcl-2, and bax and found that BTP could upregulate the C-caspase-3 and bax expression in osteoclasts and decrease the expression of bcl-2, p-Akt, and p-PI3K in a dose-dependent manner, indicating that BTP could induce PI3K/Akt mediated apoptosis in osteoclasts to treat ONFH. This study explored the pharmacodynamic basis and mechanism of BTP against ONFH from the perspective of systemic pharmacology, laying a foundation for further elucidating the therapeutic effects of BTP against ONFH.